Creation of maize hybrids of excess sugar with high level of antioxidant activity using the test system based on stable radical DPPH - Поздняков, В. В.; Харченко, Ю. В.; Харченко, Л. Я.; Анцыферова, О. В. (Scientific Progress & Innovations, 2016)
Hybrids of excess sugar maize are good raw material for the production of functional food products, including baby food and diet. Important indicators of high quality of these products are high protein content and a valuable oil, a small amount of poorly digestible maize starch and a high content of antioxidants, and also excellent taste qualities. The paper presents data on the evaluation of the antioxidant activity of a large group of promising new hybrids of excess sugar maize of mid-group created in order to obtain valuable raw materials for the canning industry. Index value of total antioxidant activity varied over a wide range (from 31,8 % to 60,4 %, 568,4–1,008 mg/g of seed), which indicates on promising use of this important parameter in the breeding of biochemical excess sugar maize on quality.